N @ P ratios in terrestrial plants: variation and functional significance - Güsewell, Sabine (The New phytologist, 2004)
Nitrogen (N) and phosphorus (P) availability limit plant growth in most terrestrial ecosystems. This review examines how variation in the relative availability of N and P, as reflected by N : P ratios of plant biomass, influences vegetation composition and functioning. Plastic responses of plants to N and P supply cause up to 50-fold variation in biomass N : P ratios, associated with differences in root allocation, nutrient uptake, biomass turnover and reproductive output. Optimal N : P ratios - those of plants whose growth is equally limited by N and P - depend on species, growth rate, plant age and plant parts. At vegetation level, N : P ratios <10 and >20 often (not always) correspond to N- and P-limited biomass production, as shown by short-term fertilization experiments; however long-term effects of fertilization or effects on individual species can be different. N : P ratios are on average higher in graminoids than in forbs, and in stress-tolerant species compared with ruderals; they correlate negatively with the maximal relative growth rates of species and with their N-indicator values. At vegetation level, N : P ratios often correlate negatively with biomass production; high N : P ratios promote graminoids and stress tolerators relative to other species, whereas relationships with species richness are not consistent. N : P ratios are influenced by global change, increased atmospheric N deposition, and conservation managment. Contents Summary 243 I Introduction 244 II Variability of N : P ratios in response to nutrient  supply 244 III Critical N : P ratios as indicators of nutrient  limitation 248 IV Interspecific variation in N : P ratios 252 V Vegetation properties in relation to N : P ratios 255 VI Implications of N : P ratios for human impacts  on ecosystems 258 VII Conclusions 259 Acknowledgements 259 References 260